2021
DOI: 10.14814/phy2.14963
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐channel degeneracy: Multiple ion channels heterogeneously regulate intrinsic physiology of rat hippocampal granule cells

Abstract: Degeneracy, the ability of multiple structural components to elicit the same characteristic functional properties, constitutes an elegant mechanism for achieving biological robustness. In this study, we sought electrophysiological signatures for the expression of ion‐channel degeneracy in the emergence of intrinsic properties of rat hippocampal granule cells. We measured the impact of four different ion‐channel subtypes—hyperpolarization‐activated cyclic‐nucleotide‐gated (HCN), barium‐sensitive inward rectifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 179 publications
1
38
0
Order By: Relevance
“…These changes are broadly consistent with an increased current passage through HCN channels, which are hyperpolarization-activated channels that mediate an inward current that is active under resting conditions. Specifically, it has been shown that increases in HCN channels and the associated h current result in depolarization of RMP, a reduction of R in , |Z| max and S a (Magee, 1998;Narayanan and Johnston, 2007;Mishra and Narayanan, 2021a;Stegen et al, 2012). We asked if other TBF-induced sub-threshold changes were also consistent with changes in HCN channels.…”
Section: Signature Changes In Several Physiological Measurements Poin...mentioning
confidence: 97%
See 4 more Smart Citations
“…These changes are broadly consistent with an increased current passage through HCN channels, which are hyperpolarization-activated channels that mediate an inward current that is active under resting conditions. Specifically, it has been shown that increases in HCN channels and the associated h current result in depolarization of RMP, a reduction of R in , |Z| max and S a (Magee, 1998;Narayanan and Johnston, 2007;Mishra and Narayanan, 2021a;Stegen et al, 2012). We asked if other TBF-induced sub-threshold changes were also consistent with changes in HCN channels.…”
Section: Signature Changes In Several Physiological Measurements Poin...mentioning
confidence: 97%
“…Synergistic interactions between HCN and inward-rectifier potassium channels mediate TBF-induced reduction in sub-threshold excitability of DG granule cells ZD7288, an HCN-channel blocker, significantly reduces sub-and supra-threshold excitability of DG granule cells (Mishra and Narayanan, 2021a). Encouraged by these strong physiological lines of evidence on the potential role of resting conductances in sub-threshold plasticity (Figure 4C-4F), we first tested the time-dependent effect of ZD7288 on the intrinsic properties of DG granule cells.…”
Section: Signature Changes In Several Physiological Measurements Poin...mentioning
confidence: 99%
See 3 more Smart Citations